PENGARUH KEPEMILIKAN, DEWAN PERUSAHAAN, MOTIVASI, DAN FAKTOR LAINNYA TERHADAP MANAJEMEN LABA - Linda Faustina; Kartina Natalylova (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical evidence about the influence of internal ownership, board size, board independence, female in board of directors, audit committee meeting frequency, tax avoidance, firm's performance, motivation debt contracts, and earnings power to earnings management on non-financial companies in Indonesia. This research was conducted on 99 non-financial companies listed on Indonesia Stock Exchange that were selected based on certain criteria with the research period from 2018 to 2020. The result of this research states that tax avoidance has an influence on earnings management. This is because an increased CETR value means companies are more compliant with tax regulations and less tax avoidance practices. While internal ownership, board size, board independence, female in board of directors, audit committee meeting frequency, firm's performance, motivation debt contracts, and earnings power have no influence on earnings management.